Personality directed approach as means of the strategy of development of the creative potential of children with developmental delay (participation) - Жилова, Юлия; Бежина, Виктория; Шаяхметова, Айсулу (Pedagogy and Psychology, 2021)
The article is devoted to the issue of personal-oriented approach. Special attention is paid to the principles of a personal-oriented approach, which determine the features of the educational environment. The author takes the position of implementing this approach through the use of educational cooperation technology, contextual teaching technology in the educational process. A parallel uniting active teaching methods: design and research activities, solving specific situations, role-playing game, business game was drawn. Based on the analysis, the author gives the concept to active methods, which are designated as a strategy for the development of the creative potential of children with developmental delay.